2009
DOI: 10.1007/s10903-008-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Reported Use of Antibiotics Amongst Immigrant Ethnic Groups in New Zealand

Abstract: Interventions to improve use of antibiotics need to be pitched at a very basic level of knowledge, and need to be targeted towards particular ethnic groups, particularly those in whose home countries antibiotics are widely available without prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…An understanding of antibiotic use is important because personal decisions are based on these understandings (Norris et al, 2010). They can impact physicians' prescription behavior (Belongia, Naimi, Gale, & Besser, 2002), as well as lead to decreasing suboptimal use of antibiotics, such as using short courses and sub-therapeutic doses (Norris et al).…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of antibiotic use is important because personal decisions are based on these understandings (Norris et al, 2010). They can impact physicians' prescription behavior (Belongia, Naimi, Gale, & Besser, 2002), as well as lead to decreasing suboptimal use of antibiotics, such as using short courses and sub-therapeutic doses (Norris et al).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibiotics are still freely available for purchase without a medical prescription in many countries, which aggravates self-medicating (4,67). Migrants from these countries may continue to pursue their inappropriate practices in the new country of residence because of their previous knowledge and experience of antibiotic use (7,92,175). Studies in New…”
Section: Discussionmentioning
confidence: 99%
“…Zealand found that misconceptions regarding antibiotics existed and the prevalence of non-prescribed antibiotic use was surprisingly high among Korean and Egyptian immigrant groups (7,175).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations